Everyday Resistance - Raksha Vasudevan (Graduate Institute Publications, 2013)
Northern Sri Lanka has been at the heart of the country's 30-year civil war, a bloody conflict which has given rise to an estimated 40,000 households headed by women in this region. Based on fieldwork conducted in 10 villages and towns, this ePaper aims to identify and describe the most pervasive economic, physical and psycho-social vulnerabilities that female heads of households (FHHs) in the north face in the post-war context. It also traces how the state has shaped these vulnerabilities th...